The transformation of property rights in Kenya's Maasiland: triggers and motivations - Mwangi, Esther (International Food Policy Research Institute, 2005)
This paper explores the puzzle of why the pastoral Maasai of Kajiado, Kenya, supported the individualization of their collectively held group ranches, an outcome that is inconsistent with theoretical expectation. Findings suggest that individuals and groups will seek to alter property rights in their anticipation of net gains from a new assignment, even as they seek to eliminate disadvantages that were present in the status quo property rights structure. Heightened perceptions of impending land scarcity, failures of collective decision making, the promise of new income opportunities and the possibility of accessing capital markets motivated individuals to support group ranch subdivision. More importantly individuals were confronted with a declining security of tenure over their lands. Their supporting a transition to individual rights also represents a rational response anticipated to secure land claims against unauthorized appropriations by both Maasai and non-Maasai elite. Given the differentiated structure of group ranch communities, the costs and benefits of property transformation were unevenly distributed. The political process yielded beneficial outcomes for those with access to decision making, while creating vulnerabilities for those with less access such as women, the youth and poor herders.